A Supply and Demand Analysis for the Turkish Electricity Market: Supply Adequacy and Resource Utilization - Selim Önay (EconJournals, 2021)
Electricity is a critical commodity for which the demand should be met using reliable, cost-effective, and sustainable resources. The characteristics of supply and demand should be comparatively analyzed for efficient electric power system planning. This study examines Turkey’s current electricity supply and demand and their characteristics for future balance. Turkey’s installed capacity and electricity consumption per capita are analyzed using historical data, and trends for future electricity demand are estimated. Electricity supply based on generation sources is reviewed, and the historical contribution of each source to total generation is shown. Statistical distribution of electricity generation by generation types and their relationships are also investigated. As the supply adequacy should be carefully reviewed for sustainability, finally, the characteristics of supply are analyzed using capacity factors, reserve margins, capacity margins, load duration curves, and peak-to-average demand ratios. It is shown that although the margins are above comfortable levels after 2017, they still need to be increased as the increased use of renewables might require extra availability. The load duration curves and peak-to-average demand ratios have shown that the density of demand is increasing, and capacity needs to be expanded and utilized carefully in the future for the reliability of the power system. Keywords: Electricity Supply-Demand, Electricity Generation Sources, Consumption Trends, Capacity Factor, Reserve Margin, Load Duration Curve JEL Classifications: Q41, O13, L94 DOI: https://doi.org/10.32479/ijeep.11412